Teams Games Tournament Assisted by Question Card Increases Student Knowledge Competence in Science Learning - Putra, Made; Oktayana Mahardika, I Kadek Dwi (International Journal of Elementary Education, 2020)
The low competence of students' science knowledge is caused by the lack of optimal use of innovative learning models and the lack of using learning media. The purpose of this study was to examine the effect of the Teams Games Tournament learning model assisted by the Media Question Card on the scientific competence of science students in fourth grade elementary. This type of research was a quasi-experimental research design with a nonequivalent control group design. The population of this study was the fourth-grade students with a total of 392 students. The sample was determined by a random sampling technique. The sample in this study was class IV with a total sample of class 34 students as the experimental group and class IV with a class sample of 33 students as the control group. The science competency data collection was done by the test method and the instrument used was an ordinary multiple-choice objective test. The data obtained were analyzed using a t-test. The results of the analysis showed that there were significant differences in the learning models of teamâ€™s games tournament assisted by the media question card to the scientific competence of science with conventional learning of fourth-grade students. Based on the results of data analysis obtained tcount = 3.245 at a significance level of 5% and dk = 65 obtained ttable = 1.997 so tcount = 3.25> ttable = 1.997. Based on the testing criteria, it is rejected and accepted. Thus, it can be concluded, the Teams Games Tournament learning model assisted by the Question Card media influences the science knowledge competence of fourth-grade.Â